Molecular Interactions between MUC1 Epithelial Mucin, β-Catenin, and CagA Proteins - Guang, Wei; Twadell, William; Lillehoj, Erik (Frontiers in Immunology, 2012)
Interleukin (IL)-8-driven neutrophil infiltration of the gastric mucosa is pathognomonic of persistent Helicobacter pylori infection. Our prior study showed that ectopic over-expression of MUC1 in human AGS gastric epithelial cells reduced H. pylori-stimulated IL-8 production compared with cells expressing MUC1 endogenously. Conversely, Muc1 knockout (Muc1-/-) mice displayed an increased level of transcripts encoding the keratinocyte chemoattractant (KC), the murine equivalent of human IL-8, in gastric mucosa compared with Muc1(+/+) mice during experimental H. pylori infection. The current study tested the hypothesis that a decreased IL-8 level observed following MUC1 over-expression is mediated through the ability of MUC1 to associate with β-catenin, thereby inhibiting H. pylori-induced β-catenin nuclear translocation. Increased neutrophil infiltration of the gastric mucosa of H. pylori-infected Muc1(-/-) mice was observed compared with Muc1(+/+) wild type littermates, thus defining the functional consequences of increased KC expression in the Muc1-null animals. Protein co-immunoprecipitation (coIP) studies using lysates of untreated or H. pylori-treated AGS cells demonstrated that (a) MUC1 formed a coIP complex with β-catenin and CagA, (b) MUC1 over-expression reduced CagA/β-catenin coIP, and (c) in the absence of MUC1 over-expression, H. pylori infection increased the nuclear level of β-catenin, (d) whereas MUC1 over-expression decreased bacteria-driven β-catenin nuclear localization. These results suggest that manipulation of MUC1 expression in gastric epithelia may be an effective therapeutic strategy to inhibit H. pylori-dependent IL-8 production, neutrophil infiltration, and stomach inflammation.